Biomedical Applications of Scutellaria edelbergii Rech. f.: In Vitro and In Vivo Approach - Muddaser Shah; Waheed Murad; Najeeb Ur Rehman; Sobia Ahsan Halim; Manzoor Ahmed; Hazir Rehman; Muhammed Zahoor; Sidra Mubin; Ajmal Khan; Mohamed A. Nassan; Gaber El-Saber Batiha; Ahmed Al-Harrasi (Molecules, 2021)
In the current study, in vitro antimicrobial and antioxidant activities and in vivo anti-inflammatory and analgesic activities of Scutellaria edelbergii Rech. f. (crude extract and subfractions, i.e., n-hexane, ethyl acetate (EtOAc), chloroform, n-butanol (n-BuOH) and aqueous) were explored. Initially, extraction and fractionation of the selected medicinal plant were carried out, followed by phytochemical qualitative tests, which were mostly positive for all the extracts. EtOAc fraction possessed a significant amount of phenolic (79.2 ± 0.30 mg GAE/g) and flavonoid (84.0 ± 0.39 mg QE/g) content. The EtOAc fraction of S. edelbergii exhibited appreciable antibacterial activity against Gram-negative (Escherichia coli and Klebsiella pneumoniae) strains and significant zones of inhibition were observed against Gram-positive bacterial strains (Bacillus subtilis and Staphylococcus aureus). However, it was found inactive against Candida Albicans and Fusarium oxysporum fungal strains. The chloroform fraction was the most effective with an IC50 value of 172 and 74 µg/mL against DPPH (1,1-Diphenyl-2-picryl-hydrazyl) and ABTS assays, in comparison with standard ascorbic acid 59 and 63 µg/mL, respectively. Moreover, the EtOAc fraction displayed significant in vivo anti-inflammatory activity (54%) using carrageenan-induced assay and significant (55%) in vivo analgesic activity using acetic acid-induced writing assay. In addition, nine known compounds, ursolic acid (UA), ovaul (OV), oleanolic acid (OA), β-sitosterol (BS), micromeric acid (MA), taraxasterol acetate (TA), 5,3′,4′-trihydroxy-7-methoxy flavone (FL-1), 5,7,4′-trihydroxy-6,3′-dimiethoxyflavone (FL-2) and 7-methoxy catechin (FL-3), were isolated from methanolic extract of S. edelbergii. These constituents have never been obtained from this source. The structures of all the isolated constituents were elucidated by spectroscopic means. In conclusion, the EtOAc fraction and all other fractions of S. edelbergii, in general, displayed a significant role as antibacterial, free radical scavenger, anti-inflammatory and analgesic agents which may be due to the presence of these constituents and other flavonoids.